Modified sulfide solid electrolyte
Patent Information
- Application Number
- JP2025058921
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0008】 本発明によれば、耐熱性及び耐酸化性に優れた改質硫化物固体電解質を提供することができる。
Smart Images

Figure 2026166148000002 
Figure 2026166148000003 
Figure 2026166148000001
Abstract
Description
[Technical Field]
[0001] This invention relates to modified sulfide solid electrolytes. [Background technology]
[0002] In recent years, with the rapid proliferation of information-related devices and communication equipment such as personal computers, video cameras, and mobile phones, the development of batteries used as power sources has become increasingly important. Traditionally, batteries used in such applications have employed electrolytes containing flammable organic solvents. However, because the electrolyte is both liquid and flammable, there are safety concerns regarding leakage, ignition, and other issues when used in batteries. In particular, in automotive applications, there is a demand for higher capacity and higher output, and concerns about the safety of conventional batteries using electrolytes are growing. Therefore, by making batteries entirely solid, it is possible to eliminate the use of flammable organic solvents within the battery, simplify safety devices, and improve manufacturing costs and productivity. As a result, development of all-solid-state batteries, in which the electrolyte is replaced with a solid electrolyte layer, is underway.
[0003] Sulfide solid electrolytes have long been known as solid electrolytes used in solid electrolyte layers. High oxidation-reduction resistance is desired for sulfide solid electrolytes, and there is also a growing demand for improved battery performance when used in lithium-ion batteries. As methods to improve these properties, techniques such as coating the surface of the solid electrolyte and using it as a composition containing the solid electrolyte and an organic compound are being investigated.
[0004] For example, Patent Document 1 describes a modified sulfide solid electrolyte that, even if it has a large specific surface area, exhibits excellent coating suitability when applied as a paste and can efficiently achieve excellent battery performance, with a specific surface area of 10 m². 2 A modified sulfide solid electrolyte has been proposed that contains a sulfide solid electrolyte of 1 / g or more and an epoxy compound, and has a predetermined peak in the infrared absorption spectrum obtained by FT-IR analysis (ATR method). [Prior art documents] [Patent Documents]
[0005]
Patent Document 1
Summary of the Invention
Problem to be Solved by the Invention
[0006] The present invention has been made in view of such circumstances, and an object thereof is to provide a modified sulfide solid electrolyte excellent in heat resistance and oxidation resistance.
Means for Solving the Problem
[0007] The modified sulfide solid electrolyte according to the present invention is A sulfide solid electrolyte having a BET specific surface area of 15 m 2 / g or more and 35 m 2 / g or less, and a coating material, In the DTA curve obtained by differential thermal analysis (DTA), the modified sulfide solid electrolyte has a crystallization peak on the higher temperature side than 265°C.
Effects of the Invention
[0008] According to the present invention, a modified sulfide solid electrolyte excellent in heat resistance and oxidation resistance can be provided.
Brief Description of the Drawings
[0009] [Figure 1] These are DTA curves obtained by differential thermal (DTA) analysis for the modified sulfide solid electrolytes of Examples 1 to 7 and the sulfide solid electrolytes of Comparative Examples 1 and 2. [Figure 2] These are CV curves of the first cycle in CV measurement for the modified sulfide solid electrolytes of Examples 1 to 7 and the sulfide solid electrolytes of Comparative Examples 1 and 2.
Modes for Carrying Out the Invention
[0010] The embodiments of the present invention (hereinafter sometimes referred to as "these embodiments") will be described below. In this specification, the upper and lower limit values related to the numerical ranges indicated by "greater than or equal to," "less than or equal to," and "~" can be any combination of values, and the values in the examples can also be used as the upper and lower limit values.
[0011] (Knowledge gained by the inventors in arriving at the present invention) The inventors of this invention diligently studied and, as a result of their efforts to solve the above problems, discovered the following and completed the present invention. As described in Patent Document 1, techniques for coating or incorporating a compound onto the surface of a sulfide solid electrolyte have existed for some time. Patent Document 1 discloses a modified sulfide solid electrolyte that, even if it has a large specific surface area, exhibits excellent coating suitability when applied as a paste and can efficiently exhibit excellent battery performance. 2 / g and 40m 2 Detailed studies have been conducted on sulfide solid electrolytes having a BET specific surface area of 1 / g. By modifying these sulfide solid electrolytes, modified sulfide solid electrolytes exhibiting excellent coating properties and superior battery performance have been obtained.
[0012] Our investigations revealed that, depending on the BET specific surface area of the sulfide solid electrolyte, it may not be possible to adequately coat its surface, thus preventing improvements in battery performance. Further investigations revealed that when a coating material is added to a sulfide solid electrolyte with a specific BET specific surface area, the resulting modified sulfide solid electrolyte exhibits a crystallization peak at temperatures above 265°C in the DTA curve obtained by differential thermal analysis, indicating improved heat resistance. This is presumed to be because when the sulfide solid electrolyte has a specific BET specific surface area, its adhesion to the coating material improves, making it easier for the coating material to cover its surface and thus blocking heat transfer to the sulfide solid electrolyte. It was also found that when the surface of the sulfide solid electrolyte is sufficiently coated with the coating material, oxidation reactions occurring at the interface between the electrolyte and the conductive material are suppressed, improving oxidation resistance.
[0013] As described above, in Patent Document 1, sulfide solid electrolytes with a BET specific surface area of 10 m 2 / g and 40 m 2 / g have been studied in detail, but the optimal BET specific surface area from the viewpoints of heat resistance and oxidation resistance has not been sufficiently investigated. Further, replacing the specific surface area of a sulfide solid electrolyte with the specific surface area described in another document does not necessarily allow the production of the same sulfide solid electrolyte as in that document, and adjustment of the specific surface area is not easy.
[0014] Based on the above studies, the present inventors have found that by adding a coating material to a sulfide solid electrolyte having a specific BET specific surface area, the resulting modified sulfide solid electrolyte has a crystallization peak on the higher temperature side than 265°C in the DTA curve obtained by differential thermal analysis, and is excellent in heat resistance and oxidation resistance. This finding has led to the completion of the present invention.
[0015] (Various aspects of the present embodiment) The modified sulfide solid electrolyte according to the first aspect of the present embodiment is a modified sulfide solid electrolyte comprising a sulfide solid electrolyte having a BET specific surface area of 15 m 2 / g or more and 35 m 2 / g or less, and a coating material, and having a crystallization peak on the higher temperature side than 265°C in the DTA curve obtained by differential thermal analysis (DTA).
[0016] In the present specification, the term "sulfide solid electrolyte" means an electrolyte that contains a sulfur atom and remains solid at 25°C under a nitrogen atmosphere. In the present embodiment, the sulfide solid electrolyte is preferably a sulfide solid electrolyte that contains a lithium atom, a sulfur atom, a phosphorus atom and a halogen atom, and has ionic conductivity attributable to the lithium atom.
[0017] The term "sulfide solid electrolyte" includes both crystalline sulfide solid electrolytes having a crystal structure and amorphous sulfide solid electrolytes. In this specification, a crystalline sulfide solid electrolyte is a solid electrolyte in which a peak originating from the solid electrolyte is observed in the X-ray diffraction pattern in an X-ray diffraction measurement, regardless of whether or not a peak originating from the raw material of the solid electrolyte is observed. That is, a crystalline sulfide solid electrolyte includes a crystalline structure derived from the solid electrolyte, and may be partially derived from the solid electrolyte or entirely derived from the solid electrolyte. Furthermore, if a crystalline sulfide solid electrolyte has the above-described X-ray diffraction pattern, it may also contain amorphous sulfide solid electrolyte (also referred to as "glass component"). Therefore, crystalline sulfide solid electrolytes include so-called glass ceramics obtained by heating amorphous sulfide solid electrolyte (glass component) above its crystallization temperature.
[0018] Furthermore, in this specification, amorphous sulfide solid electrolytes (glass components) refer to those that exhibit a halo pattern in X-ray diffraction measurements where peaks other than those originating from the raw materials are substantially absent, regardless of whether or not peaks originating from the raw materials of the solid electrolyte are present. The above distinction between crystalline and amorphous materials applies to both sulfide solid electrolytes and modified sulfide solid electrolytes in this embodiment.
[0019] As previously described, depending on the BET specific surface area of the sulfide solid electrolyte, it may not be possible to adequately coat its surface, and thus the battery performance may not be improved. The inventors have found that when a coating material is added to a sulfide solid electrolyte having a specific BET specific surface area, the resulting modified sulfide solid electrolyte has a crystallization peak at temperatures above 265°C in the DTA curve obtained by differential thermal analysis, and its heat resistance and oxidation resistance are improved. In other words, the modified sulfide solid electrolyte of this embodiment has properties of heat resistance and oxidation resistance that have been "modified," and should be called a "modified sulfide solid electrolyte."
[0020] The modified sulfide solid electrolyte according to the second embodiment of this invention is, in the first embodiment described above, The content of the coating material is 1.0% by mass or more and 10.0% by mass or less based on 100% by mass of the sulfide solid electrolyte. That is the case.
[0021] In this embodiment, if the content of the coating material is within the above range, the coating material can sufficiently cover the surface of the sulfide solid electrolyte, thereby improving its heat resistance and oxidation resistance.
[0022] The modified sulfide solid electrolyte according to the third embodiment of this embodiment is, in the first or second embodiment described above, The coating material is a compound having an epoxy group. That is the case.
[0023] In this embodiment, if the coating material of the modified sulfide solid electrolyte is a compound having an epoxy group, the adhesion between the surface of the sulfide solid electrolyte and the coating material is improved, the surface is more easily covered by the coating material, and the heat resistance and oxidation resistance can be improved.
[0024] The modified sulfide solid electrolyte according to the fourth embodiment of this embodiment is, in any one of the first to third embodiments described above, The sulfide solid electrolyte comprises lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms. That is the case.
[0025] In this embodiment, the modified sulfide solid electrolyte exhibits improved ionic conductivity due to the inclusion of the above-mentioned constituent atoms in the sulfide solid electrolyte.
[0026] The modified sulfide solid electrolyte according to the fifth embodiment of this embodiment is, in any one of the first to fourth embodiments described above, The decrease rate of the oxidation current measured by cyclic voltammetry (CV measurement), calculated using the following formula, is 10% or more. That is the case. The percentage decrease in oxidation current (%) = (oxidation current 2 - oxidation current 1) / oxidation current 2 × 100 Oxidation current 1: Oxidation current (μA) of the modified sulfide solid electrolyte. Oxidation current 2: Oxidation current (μA) of the sulfide solid electrolyte before modification.
[0027] The higher the numerical value of the above-mentioned reduction rate of oxidation current, the better the oxidation resistance. Therefore, in this embodiment, if the reduction rate of oxidation current of the modified sulfide solid electrolyte is equal to or greater than the above value, then superior oxidation resistance can be obtained.
[0028] The modified sulfide solid electrolyte according to the sixth embodiment of this invention is, in any one of the first to fifth embodiments described above, The sulfide solid electrolyte contains a thiolysicon region type II crystal structure. That is the case.
[0029] In this embodiment, the modified sulfide solid electrolyte exhibits improved ionic conductivity because the sulfide solid electrolyte contains a thiolysicon region type II crystal structure.
[0030] The modified sulfide solid electrolyte of this embodiment will be described in more detail below, in accordance with the above-described aspects.
[0031] [Modified sulfide solid electrolyte] The modified sulfide solid electrolyte of this embodiment is BET specific surface area is 15m 2 / g or more 35m 2 It comprises a sulfide solid electrolyte in a quantity of less than / g and a coating material. This modified sulfide solid electrolyte exhibits a crystallization peak at temperatures above 265°C in the DTA curve obtained by differential thermal analysis (DTA).
[0032] In differential thermal analysis (DTA), the higher the crystallization peak is located on the high-temperature side of the DTA curve, the higher the crystallization temperature and the better the heat resistance. The modified sulfide solid electrolyte of this embodiment exhibits excellent heat resistance, as evidenced by the crystallization peak at temperatures above 265°C in the DTA curve obtained by differential thermal analysis (DTA). From the viewpoint of further improving heat resistance, the modified sulfide solid electrolyte of this embodiment preferably has the crystallization peak at 270°C or higher, more preferably 280°C or higher, and even more preferably 290°C or higher. The crystallization peak described above can be made to be greater than or equal to the above value by appropriately adjusting the BET specific surface area of the sulfide solid electrolyte and the content of the coating material. In this specification, the crystallization peak was measured using a differential thermal analyzer (DTA) under a heating condition of 10°C / min.
[0033] The modified sulfide solid electrolyte of this embodiment comprises a sulfide solid electrolyte having the above-mentioned specific BET specific surface area (hereinafter also simply referred to as "sulfide solid electrolyte") and a coating material. As a result, the modified sulfide solid electrolyte has excellent heat resistance and oxidation resistance. As previously mentioned, it is presumed that when a sulfide solid electrolyte has a specific BET specific surface area, its adhesion to the coating material improves, making it easier for the coating material to cover its surface, thereby blocking heat transfer to the sulfide solid electrolyte and improving its heat resistance. Furthermore, when the surface of the sulfide solid electrolyte is sufficiently covered with the coating material, oxidation reactions occurring at the interface between the electrolyte and the conductive material are suppressed, improving oxidation resistance.
[0034] In this embodiment, the modified sulfide solid electrolyte may have the coating material attached so as to cover the entire surface of the sulfide solid electrolyte, or it may have the coating material attached so as to cover a portion of the surface of the sulfide solid electrolyte, or either is acceptable. The more the surface of the sulfide solid electrolyte is covered by the coating material, the better the heat resistance and oxidation resistance of the resulting modified sulfide solid electrolyte will be. Furthermore, the presence of a coating material on the surface of the sulfide solid electrolyte can be confirmed, for example, by analyzing the surface composition of the sulfide solid electrolyte.
[0035] (Sulfide solid electrolyte) The sulfide solid electrolyte used in this embodiment has a BET specific surface area of 15 m². 2 / g or more 35m 2 The BET specific surface area of the sulfide solid electrolyte is less than or equal to / g. When the BET specific surface area of the sulfide solid electrolyte is within the above range, adhesion to the coating material is improved, and its surface is more easily covered by the coating material. As a result, the resulting modified sulfide solid electrolyte has excellent heat resistance and oxidation resistance. From this viewpoint, the above BET specific surface area is preferably 18m². 2 / g or more 32m 2 / g or less, more preferably 20m 2 / g or more 30m 2 It is less than / g. In this specification, the BET specific surface area is the specific surface area measured using nitrogen gas as the adsorbate, in accordance with JIS Z 8830:2013 (Method for measuring the specific surface area of powders (solids) by gas adsorption).
[0036] The sulfide solid electrolyte used in this embodiment preferably contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms. The inclusion of these constituent atoms in the sulfide solid electrolyte further improves its ionic conductivity.
[0037] (Manufacturing of sulfide solid electrolytes) The sulfide solid electrolyte that can be used in this embodiment contains sulfur atoms and has a BET specific surface area of 15 m². 2 / g or more 35m 2 Any product with a concentration of less than / g can be used without any particular restrictions; commercially available products can be used as is, or products can be manufactured and used. The method for producing and using a sulfide solid electrolyte that can be used in this embodiment will be described. The sulfide solid electrolyte that can be used in this embodiment is obtained by a production method that includes mixing two or more raw materials selected from compounds containing at least one atom of the following: lithium, sulfur, phosphorus, and halogen.
[0038] (raw materials) As raw materials, two or more compounds selected from compounds containing at least one atom from the following groups may be used: lithium, sulfur, phosphorus, and halogen. Compounds that can be used as raw materials contain at least one atom from lithium, sulfur, phosphorus, and halogen atoms. More specifically, raw materials containing at least two atoms selected from the above atoms, such as lithium sulfide; phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); and raw materials consisting of one atom selected from the above atoms, such as elemental phosphorus and elemental sulfur, are typically preferred. Among these, lithium sulfide and phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5) are preferred, and among phosphorus sulfides, phosphorus pentasulfide (P2S5) is preferred.
[0039] Furthermore, substances containing halogen atoms can also be used as raw materials. For example, lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; and elemental halogens such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2) are typically preferred.
[0040] The above raw materials can be used by blending them in a ratio that matches the composition of a sulfide solid electrolyte having a desired crystal structure. Examples of the blending ratio of lithium sulfide to other raw materials include those described in International Publication No. 2020 / 105737 (see paragraphs
[0024] to
[0028] ), etc. Furthermore, the raw materials can be appropriately selected from the substances exemplified in International Publication No. 2020 / 105737 (see paragraphs
[0020] to
[0022] ), etc.
[0041] (mixture) The mixing of two or more raw materials selected from compounds containing at least one atom of lithium, sulfur, phosphorus, and halogen is not particularly limited in terms of the method, as long as the above raw materials can be mixed. For example, it can be done using a pulverizer, mixer, agitator, etc. Using a pulverizer will result in the pulverization of the raw materials, but mixing will also occur simultaneously. Mixing of raw materials can also occur when using a mixer and agitator. Therefore, it can be said that the sulfide solid electrolyte that can be used in this embodiment can preferably be produced by stirring, mixing, pulverizing, or a combination of any of the following processes using two or more raw materials selected from substances containing at least one atom of lithium, sulfur, phosphorus, and halogen.
[0042] Regarding the equipment used for mixing raw materials, such as pulverizers, mixers, and agitators, there are no particular restrictions on the use of commonly available equipment.
[0043] In the above mixing process, a solvent can be added to the above raw materials and mixed. A wide range of solvents conventionally used in the production of solid electrolytes can be used as the solvent, including, for example, hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents.
[0044] In addition to the hydrocarbon solvents mentioned above, solvents containing heteroatoms other than carbon and hydrogen atoms, such as nitrogen, oxygen, sulfur, and halogen atoms, can also be used. Such solvents have the property of readily forming complexes (which can also be called "electrolyte precursors" because a sulfide solid electrolyte can be obtained by removing the complexing agent from the "complex") with raw materials containing lithium, phosphorus, sulfur, and halogen atoms (hereinafter, such solvents will also be called "complexing agents"). They have the property of making it easier to retain halogen atoms within the structure of the sulfide solid electrolyte, which is useful in that higher ionic conductivity can be obtained. Furthermore, when complexing agents are used, the reaction of the raw materials can be carried out simply by using equipment such as mixers and stirrers, that is, without using a pulverizer, which is useful.
[0045] As the complexing agent and hydrocarbon solvent that can be used, for example, the complexing agents and hydrocarbon solvents exemplified in International Publication No. 2020 / 105737, etc., can be used. As a complexing agent, among solvents containing these heteroatoms, it is preferable to use a solvent containing a nitrogen atom, more preferably an amine solvent having an amino group, and even more preferably a diamine solvent having two amino groups.
[0046] (Drying) If mixing is performed using a solvent, the mixture may be dried after mixing (usually a slurry). If a complexing agent is used as the solvent, the sulfide solid electrolyte is obtained by removing the complexing agent from the complex containing the complexing agent; if a complexing agent and a solvent are used in combination, the complexing agent is removed from the complex containing the complexing agent and the solvent is removed; and if a solvent other than a complexing agent is used, the solvent is removed. The obtained sulfide solid electrolyte exhibits ionic conductivity due to lithium atoms.
[0047] The drying method can be any method that can remove the solvent, and can be performed using solid-liquid separation, drying by heating, reduced-pressure drying (vacuum drying), or a combination of these methods. When using a complexing agent as a solvent to remove the complexing agent from the complex (electrolyte precursor), drying by heating is preferred, and it is preferable to carry out the drying using a dryer such as a flow-through heater. Since the complexing agent can be removed from the complex (electrolyte precursor) quickly, the generation of impurities can be suppressed more efficiently, and a high-quality sulfide solid electrolyte can be obtained. Preferred flow-through heaters include airflow dryers, spray dryers, and fluidized bed dryers using a medium, with airflow dryers being the most preferred among them.
[0048] (heating) When producing a crystalline sulfide solid electrolyte, further heating may be included. If an amorphous sulfide solid electrolyte (glass component) is obtained by the above mixing, heating will yield a crystalline sulfide solid electrolyte. If a crystalline sulfide solid electrolyte is obtained, a crystalline sulfide solid electrolyte with improved crystallinity can be obtained. In either case, heating can make the obtained sulfide solid electrolyte a crystalline sulfide solid electrolyte and improve its ionic conductivity. In other words, the above heating can be considered an operation performed for crystallization.
[0049] When a complexing agent is used as a solvent during mixing, a complex containing the complexing agent is formed. However, by heating without drying as described above, the complexing agent can be removed from the complex, and a sulfide solid electrolyte can be obtained. Depending on the heating conditions, it can be amorphous or crystalline.
[0050] (Amorphous sulfide solid electrolyte) The amorphous sulfide solid electrolyte obtained by the above method contains lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms. Typical examples include sulfide solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr; and preferably sulfide solid electrolytes further containing other atoms such as oxygen atoms and silicon atoms, such as Li2S-P2S5-Li2O-LiI and Li2S-SiS2-P2S5-LiI. From the viewpoint of obtaining higher ionic conductivity, sulfide solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr, are preferred, and sulfide solid electrolytes composed of lithium sulfide, phosphorus sulfide, and two types of lithium halide, such as Li2S-P2S5-LiI-LiBr, are more preferred. The types of atoms constituting amorphous sulfide solid electrolytes can be determined, for example, by an ICP emission spectrometer.
[0051] In amorphous sulfide solid electrolytes, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms is preferably 1.0~1.8:0.1~0.8:1.0~2.0:0.01~0.6, more preferably 1.1~1.7:0.2~0.6:1.2~1.8:0.05~0.5, and even more preferably 1.2~1.6:0.25~0.5:1.3~1.7:0.08~0.4. Furthermore, when bromine and iodine, or bromine and chlorine are used in combination as halogen atoms, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, bromine, and iodine (or chlorine) is preferably 1.0~1.8:0.1~0.8:1.0~2.0:0.01~0.3:0.01~0.3, more preferably 1.1~1.7:0.2~0.6:1.2~1.8:0.02~0.25:0.02~0.25, even more preferably 1.2~1.6:0.25~0.5:1.3~1.7:0.03~0.2:0.03~0.2, and even more preferably 1.35~1.45:0.3~0.45:1.4~1.7:0.04~0.18:0.04~0.18.
[0052] There are no particular restrictions on the shape of amorphous sulfide solid electrolytes, but for example, particulate form can be used. The average particle size (D) of the particulate amorphous sulfide solid electrolyte. 50 Examples of these ranges include 0.01 μm to 500 μm and 0.1 μm to 200 μm.
[0053] (Crystalline sulfide solid electrolyte) The crystalline sulfide solid electrolyte obtained by the above method may be a so-called glass ceramic obtained by heating an amorphous sulfide solid electrolyte above its crystallization temperature, and its crystal structure may be Li3PS4, Li4P2S6, Li7PS6, or Li7P3S 11 Examples include crystal structures, and crystal structures having peaks near 2θ = 20.2° and 23.6° (for example, Japanese Patent Publication No. 2013-16423).
[0054] Li 4-x Ge 1-x P x S4-type thio-LISICON Region II crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148(7)A742-746 (2001)), Li 4-x Ge 1-x P x Other examples include crystal structures similar to the S4-type thio-LISICON Region II (see Solid State Ionics, 177 (2006), 2721-2725). Among the above, the thio-LISICON Region II type crystal structure is preferred for crystalline sulfide solid electrolytes obtained by the above method because it provides higher ionic conductivity. Here, "thio-LISICON Region II type crystal structure" refers to Li 4-x Ge 1-x P x S4-type thio-LISICON Region II crystal structure, Li 4-x Ge 1-x P x This indicates that the crystal structure is one of the S4-type thio-LISICON Region II or similar crystal structures. As will be discussed later, the thio-LISICON Region II crystal structure and the similar crystal structures are very similar in structure. Therefore, it is technically reasonable to treat the "thio-LISICON Region II crystal structure" as encompassing both the thio-LISICON Region II crystal structure and the similar crystal structures.
[0055] Here, if the sulfide solid electrolyte obtained by the above method contains lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms, then "Li 4-x Ge 1-x P x In the "S4 system thio-LISICON Region II type", "Li 4-x Ge1-x P x The compositional formula "S4" may not always be applicable. However, if it has the same diffraction peak as the "thiolysicon region type II crystal structure" (including the "similar crystal structure" above), then the sulfide solid electrolyte obtained by the above method can be said to have a thiolysicon region type II crystal structure formed by lithium atoms, phosphorus atoms, and sulfur atoms, preferably halogen atoms.
[0056] In X-ray diffraction measurements using CuKα rays, diffraction peaks for the Li3PS4 crystal structure appear, for example, around 2θ = 17.5°, 18.3°, 26.1°, 27.3°, and 30.0°, diffraction peaks for the Li4P2S6 crystal structure appear, for example, around 2θ = 16.9°, 27.1°, and 32.5°, diffraction peaks for the Li7PS6 crystal structure appear, for example, around 2θ = 15.3°, 25.2°, 29.6°, and 31.0°, and Li7P3S 11 Diffraction peaks of the crystal structure appear, for example, around 2θ = 17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, Li 4-x Ge 1-x P x The diffraction peaks of the S4-type thio-LISICON Region II crystal structure appear, for example, around 2θ = 20.1°, 23.9°, and 29.5°, and Li 4-x Ge 1-x P x Diffraction peaks for crystal structures similar to the S4-type thio-LISICON Region II appear, for example, around 2θ = 20.2° and 23.6°. Note that these peak positions may vary within a range of ±0.5°.
[0057] The crystalline sulfide solid electrolyte obtained by the above method may contain the above-mentioned thiolysicon region type II crystal structure, or it may contain it as the main crystal, but from the viewpoint of obtaining higher ionic conductivity, it is preferable that it contains it as the main crystal. In this specification, "contained as the main crystal" means that the proportion of the target crystal structure in the crystal structure is 80% or more, preferably 90% or more, and more preferably 95% or more. Furthermore, from the viewpoint of obtaining higher ionic conductivity, the crystalline sulfide solid electrolyte obtained by the above method is preferably free of crystalline Li3PS4 (β-Li3PS4).
[0058] The composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms in a crystalline sulfide solid electrolyte is the same as the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms in the amorphous sulfide solid electrolyte described above.
[0059] There are no particular restrictions on the shape of the crystalline sulfide solid electrolyte, but for example, particulate form can be used. The average particle size (D) of the particulate crystalline sulfide solid electrolyte. 50 Examples of these ranges include 0.01 μm to 500 μm and 0.1 μm to 200 μm.
[0060] (covering material) The coating material used in this embodiment coats the surface of the sulfide solid electrolyte and has excellent heat resistance and oxidation resistance. The above-mentioned coating material is not particularly limited as long as it can coat the surface of the sulfide solid electrolyte, and examples include 1,2-butylene oxide, 1,2-epoxyoctane, 1,2-epoxyoctadecane, 2,2,3,3,4,4,5,5,5-nonafluoropentyloxirane, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, 4-tert-butylphenyl glycidyl ether, (S)-glycidyl trityl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol Diglycidyl ether, neopentyl glycol diglycidyl ether, diethylene glycol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, diglycidyl resorcinol ether, 1,4-diglycidyloxybenzene, bisphenol A diglycidyl ether, 9,9-bis(4-glycidyloxyphenyl)fluorene, bisphenol A propoxylate diglycidyl ether, 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane, trimethylolpropane triglycidyl A Tel, Tris(4-hydroxyphenyl)methane triglycidyl ether, 2,4,6,8-tetramethyl-2,4,6,8-tetrakis(propylglycidyl ether)cyclotetrasiloxane, 1,3-butadiene diepoxide, 1,5-hexadiene diepoxide, 1,7-octadiene diepoxide, 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bisoxiran, N,N-diglycidyl-4-glycidyloxyaniline, 4,4'-methylenebis(N,N-diglycidylaniline), polypropylene Compounds having epoxy groups, glycidyl groups, and glycidyl ether groups, such as pyrene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, pentaerythritol glycidyl ether, PSS-octa[(3-glycidyloxypropyl)dimethylsiloxy] substitutions, and other epoxy groups; compounds having epoxy groups and silyl groups, such as tert-butyldimethylsilyl(S)-glycidyl ether and 1,1,1,3,5,5,5-heptamethyl-3-(3-glycidyloxypropyl)trisiloxane;Organic halides such as butyl iodide, octyl iodide, dodecyl iodide, benzyl bromide, 4-(trifluoromethyl)benzyl bromide, pentafluorobenzyl bromide, hexanoyl chloride, decanoyl chloride, 3,3-dimethylbutyryl chloride, octyl chloroformate, trimethylsilyl chloride; 1,4-bis(2-tetrahydroflyloxy)butane, 1,3-bis[2-(7-oxabicyclo[4.1.0]heptane- Compounds comprising two or more heterocyclic rings having carbon and oxygen atoms, such as 3-yl)ethyl]-1,1,3,3-tetramethyldisiloxane (heteropolycyclic compounds); compounds having a formyl group (CH(=O)-), such as hexanal, heptanal, undecanal, benzyloxyacetaldehyde, and 2-[(tert-butyldimethylsilyl)oxy]acetaldehyde; compounds with one or more acetyl groups (C) such as acetylacetone and benzyloxyacetone. Compounds having H3C(=O)-); compounds having two or more halogen-containing groups represented by -CH2X (where X represents a fluorine atom or a bromine atom) and organic groups, such as 1,3-dibromopropane, 1,4-dibromobutane, 1,6-dibromohexane, and 1,10-dibromodecane; thiol compounds such as 1-dodecanethiol, 1,10-decanedithiol, and 3-mercaptopropyltrimethoxysilane; tri-n-octylphosphine oxide, Examples include metal-free phosphorus compounds such as tri-n-octylphosphine, triphenylphosphine, 1,4-bis(diphenylphosphino)butane, bis[(2-diphenylphosphino)phenyl] ether, and 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene (however, these compounds do not contain oxygen atoms that form a single bond with the phosphorus atom); and metal-free boron compounds such as tri-n-octyl borate and tri-n-octadecyl borate. The above-mentioned covering materials can be used individually or in combination of several types.
[0061] From the viewpoint of improving the heat resistance and oxidation resistance of the resulting modified sulfide solid electrolyte, the above coating material is preferably a compound having a group selected from epoxy groups, glycidyl groups, and glycidyl ether groups; a compound having an epoxy group and a silyl group; a compound having a formyl group; or an organic halide. More preferably, the coating material is a compound having a group selected from epoxy groups, glycidyl groups, and glycidyl ether groups, and a compound having an epoxy group and a silyl group. Even more preferably, 4-tert-butylphenyl glycidyl ether, 2-ethylhexyl glycidyl ether, and 1,1,1,3,5,5,5-heptamethyl-3-(3-glycidyloxypropyl)trisiloxane are used.
[0062] The content of the above coating material is preferably 1.0% to 10.0% by mass, more preferably 1.0% to 5.0% by mass, and even more preferably 3.5% to 5.0% by mass, based on 100% by mass of the sulfide solid electrolyte. When the content of the above coating material is within the above range, the coating material can sufficiently cover the surface of the sulfide solid electrolyte, thereby improving heat resistance and oxidation resistance.
[0063] The coverage rate of the above coating material is preferably 60% or more, more preferably 75% or more, even more preferably 85% or more, and even more preferably 100%, based on the surface area of the sulfide solid electrolyte, i.e., the entire surface is covered. The thickness of the coating material is preferably 0.5 nm or more, more preferably 1 nm or more, with an upper limit of preferably 30 nm or less, and more preferably 25 nm or less. The thickness of the coating material can be measured by cross-sectional observation using a transmission electron microscope (TEM), and the coverage rate can be calculated from the thickness of the coating material, elemental analysis values, and BET specific surface area.
[0064] (Manufacturing of modified sulfide solid electrolytes) The modified sulfide solid electrolyte of this embodiment has, for example, a BET specific surface area of 15 m². 2 / g or more 35m 2It can be obtained by a manufacturing method comprising mixing a sulfide solid electrolyte, which is less than or equal to / g and preferably contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, a coating material, and an organic solvent, and then removing the organic solvent. The sulfide solid electrolyte described above is the same as the sulfide solid electrolyte described as usable in the modified sulfide solid electrolyte of this embodiment. Therefore, a commercially available product may be used as the sulfide solid electrolyte, or one manufactured by the method for producing the sulfide solid electrolyte described above may be used. Furthermore, the coating material described in the (coating material) section above may be used.
[0065] Examples of the above-mentioned organic solvents include, for example, the solvents described as usable in the method for producing the above-mentioned sulfide solid electrolyte. From the viewpoint of promoting the mixing of the sulfide solid electrolyte and the coating material, efficiently obtaining a modified sulfide solid electrolyte containing the sulfide solid electrolyte and the coating material, and further from the viewpoint of promoting the adhesion of the coating material to the sulfide solid electrolyte, among the above-mentioned solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, and the ether solvents, ester solvents, and nitrile solvents exemplified as complexing agents are preferred, with aromatic hydrocarbon solvents being more preferred. The above organic solvents can be used individually or in combination of several types.
[0066] The method for mixing the sulfide solid electrolyte, the coating material, and the organic solvent can be carried out by the same method as the "mixing" in the method for producing the sulfide solid electrolyte described above.
[0067] The removal of the organic solvent can be carried out by the same method as "drying" in the above-mentioned method for producing sulfide solid electrolytes. Furthermore, the "heating" step in the method for producing the sulfide solid electrolyte described above may also be performed.
[0068] (Properties of modified sulfide solid electrolytes) The modified sulfide solid electrolyte of this embodiment has a BET specific surface area of 15 m².2 / g or more 35m 2 It is less than / g, and from the viewpoint of having better heat resistance and oxidation resistance, it is preferably 18m 2 / g or more 32m 2 / g or less, more preferably 20m 2 / g or more 30m 2 It is less than / g. Even if the surface of the modified sulfide solid electrolyte is covered with a coating material, it does not significantly affect the BET specific surface area of the sulfide solid electrolyte, and the BET specific surface area of the sulfide solid electrolyte used in this embodiment and the BET specific surface area of the modified sulfide solid electrolyte are substantially the same. Therefore, as a sulfide solid electrolyte, the BET specific surface area is 15 m². 2 / g or more 35m 2 If a substance of less than / g is used, the BET specific surface area of the modified sulfide solid electrolyte will naturally be 15m². 2 / g or more 35m 2 This will be less than / g.
[0069] The oxidation current of the modified sulfide solid electrolyte in this embodiment is preferably reduced by 10% or more, more preferably by 15% or more, and even more preferably by 20% or more. Here, the reduction rate of the oxidation current is calculated by the following formula. If the rate of decrease in the oxidation current is greater than or equal to the above value, superior oxidation resistance can be obtained.
[0070] The percentage decrease in oxidation current (%) = (oxidation current 2 - oxidation current 1) / oxidation current 2 × 100 Oxidation current 1: Oxidation current (μA) of the modified sulfide solid electrolyte. Oxidation current 2: Oxidation current (μA) of the sulfide solid electrolyte before modification.
[0071] Furthermore, the oxidation current of the modified sulfide solid electrolyte in this embodiment cannot be stated definitively as an absolute value because it can vary depending on the measurement conditions, etc. However, when measured using the oxidation current measurement method described later in the examples, it is preferably 0.52 μA or less, more preferably 0.50 μA or less, and even more preferably 0.45 μA or less.
[0072] The ionic conductivity of the modified sulfide solid electrolyte in this embodiment is typically 0.5 mS / cm or higher, and furthermore, it is 1.0 mS / cm or higher, 1.2 mS / cm or higher, and 1.5 mS / cm or higher, resulting in a lithium battery with high ionic conductivity and excellent battery performance.
[0073] (Application) The modified sulfide solid electrolyte of this embodiment has excellent heat resistance and oxidation resistance, as well as high ionic conductivity, and therefore exhibits excellent battery performance, making it suitable for use in batteries. The modified sulfide solid electrolyte of this embodiment may be used in the positive electrode layer, the negative electrode layer, or the electrolyte layer. Each layer can be manufactured by known methods.
[0074] (electrode composite material) When the modified sulfide solid electrolyte of this embodiment is used as an electrode mixture, it can be used as an electrode mixture containing the modified sulfide solid electrolyte and an electrode active material. As electrode active materials, positive electrode active materials and negative electrode active materials are selected depending on whether the electrode composite material is used as the positive electrode or the negative electrode. Conventional active materials can be used for the positive electrode and negative electrode active materials. In addition to the modified sulfide solid electrolyte and electrode active material, the product may also contain other components such as conductive materials and binders.
[0075] (Lithium-ion battery) When the modified sulfide solid electrolyte of this embodiment is used as a battery, it can be used as a lithium-ion battery containing at least one of the above-mentioned modified sulfide solid electrolyte and the above-mentioned electrode composite material. Furthermore, the above-mentioned battery preferably uses a current collector in addition to the positive electrode layer, electrolyte layer, and negative electrode layer, and known current collectors can be used. For example, a layer coated with gold or the like, which reacts with the above-mentioned solid electrolyte, such as gold, Pt, Al, Ti, or Cu, can be used. [Examples]
[0076] The present invention will now be specifically described with reference to examples, but the present invention is not limited in any way by these examples.
[0077] (Manufacturing Example 1: Preparation of sulfide solid electrolyte) In a Schlenk flask (capacity: 100 mL) containing a stirring bar, 0.59 g of lithium sulfide, 0.95 g of phosphorus pentasulfide, 0.19 g of lithium bromide, and 0.28 g of lithium iodide were introduced under a nitrogen atmosphere. After rotating the stirring bar, 20 mL of the complexing agent tetramethylethylenediamine (TMEDA) was added, and stirring was continued for 12 hours. The resulting complex-containing material was dried under vacuum (room temperature: 23°C) to obtain a complex powder. Next, the complex powder was heated under vacuum at 120°C for 2 hours to obtain an amorphous sulfide solid electrolyte. Furthermore, the amorphous sulfide solid electrolyte was heated under vacuum at 140°C for 1.5 hours while shaking well to obtain a crystalline sulfide solid electrolyte (the heating temperature for obtaining the crystalline sulfide solid electrolyte (140°C in this example) is sometimes referred to as the "crystallization temperature"). The BET specific surface area of the obtained amorphous sulfide solid electrolyte and crystalline sulfide solid electrolyte was measured, and both were found to be 25 m². 2 It was / g.
[0078] (Example 1) In a Schlenk flask (capacity: 100 mL) with a stirring bar, 3 g of the crystalline sulfide solid electrolyte obtained in Production Example 1 was weighed and added under a nitrogen atmosphere. 22 g of toluene was added and the mixture was stirred to form a slurry. To this slurry, 0.03 g of 4-tert-butylphenyl glycidyl ether (1.0 mass%) was added as a coating agent (1.0 mass%) relative to 100 mass% of the crystalline sulfide solid electrolyte). After stirring for 24 hours, the toluene was removed by vacuum drying to obtain a modified sulfide solid electrolyte. The obtained modified sulfide solid electrolyte was subjected to differential thermal analysis (DTA), CV measurement (oxidation current), and ionic conductivity measurement based on the following methods. Furthermore, the rate of decrease in oxidation current was calculated based on the following methods. The measurement and calculation results are shown in Table 1.
[0079] (Examples 2-7 and Comparative Examples 1, 2) A modified sulfide solid electrolyte was prepared in the same manner as in Example 1, except that the amount of coating material used was as shown in Table 1. The obtained modified sulfide solid electrolyte was subjected to differential thermal analysis (DTA), CV measurement (oxidation current), and ionic conductivity measurement based on the following methods. Furthermore, the rate of decrease in oxidation current was calculated based on the following methods. The measurement and calculation results are shown in Table 1.
[0080] (1) Differential thermal analysis (DTA) measurement (crystallization peak temperature) DTA measurements were performed on the (modified) sulfide solid electrolytes obtained in the examples and comparative examples under the following conditions. Focusing on the exothermic peak observed below 350°C during the heating process, a linear baseline was set on the exothermic peak curve, and the difference between the intensity at each point and the baseline was taken to obtain the DTA curve. The crystallization peak temperature (°C) was read from this curve. Measurement equipment: Thermogravimetric analyzer (Mettler-Toledo TGA / DSC3+) Measurement conditions: Under a flow of 60 mL / min of N2 gas, the sample was held at 25°C for 10 minutes, then the temperature was increased to 600°C at a rate of 10°C / min.
[0081] Figure 1 shows the DTA curves obtained by differential thermal analysis (DTA) for the modified sulfide solid electrolytes of Examples 1 to 7 and the sulfide solid electrolytes of Comparative Examples 1 and 2.
[0082] (2) CV measurement (oxidation current) The following CV measurement cell was used to evaluate the oxidation current. 100 mg of solid electrolyte for the separator layer was added to a 10 mm diameter measuring cell and pressed three times at 400 MPa using a uniaxial press. Between each press, the cell was rotated 120°, and the third press was held for 5 minutes. Next, 100 mg of the solid electrolyte obtained in the example or comparative example was added and pressed three times in the same manner. Furthermore, the cell was inverted and pressed at 400 MPa for 5 minutes. Carbon-coated aluminum foil was placed on top of the solid electrolyte of the example or comparative example as a current collector foil. Li / Cu foil (φ10 mm, 0.03 / 0.01 mmt) was placed on the opposite side of the solid electrolyte for the separator layer from the solid electrolyte of the example or comparative example, and pressed at 40 MPa for 5 minutes. The cell was fastened with M8 bolts at 8 N·m to complete the measuring cell.
[0083] The electrolyte for the separator described above was synthesized under the following conditions. In a 1L reaction vessel equipped with a stirring blade, 20.5g of Li2S, 33.1g of P2S5, 10.0g of LiI, and 6.5g of LiBr were added under a nitrogen atmosphere. After rotating the stirring blade, 630g of toluene was introduced, and the slurry was stirred for 10 minutes. The reaction vessel was connected to a bead mill capable of circulating operation ("Star Mill LMZ015 (product name)", manufactured by Ashizawa Fine Tech Co., Ltd., zirconia bead material: zirconia, bead diameter: 0.5mmφ, bead usage: 456g), and a grinding process was performed for 45 hours (pump flow rate: 650mL / min, bead mill peripheral speed: 12m / min, mill jacket temperature: 45℃). The obtained slurry was dried at room temperature under vacuum (25°C) and then heated (80°C) to obtain an amorphous white powder of sulfide solid electrolyte. Furthermore, the obtained white powder was heated at 195°C for 2 hours under vacuum to obtain a crystalline white powder of sulfide solid electrolyte. In the XRD spectrum of the crystalline sulfide solid electrolyte, crystallization peaks were detected at 2θ = 20.2° and 23.6°, confirming that it has a thiolysicon region type II crystal structure. In addition, the average particle size (D) of the obtained crystalline sulfide solid electrolyte was determined. 50 The sieve diameter was 4.5 μm, and the ionic conductivity was 5.0 mS / cm.
[0084] The obtained measurement cell was connected to a measuring instrument ("VMP-3 (model number)", manufactured by Biologic), and a CV curve was obtained under the following conditions. The maximum current in the CV curve was defined as the oxidation current. Measurement temperature: 25℃ Sweep speed: 0.1mV / s Potential measurement range: Open circuit voltage (+2.7V) → +5.0V → +2.7V Number of cycles: 5
[0085] Figure 2 shows the CV curves for the first cycle of the above CV measurement for the modified sulfide solid electrolytes of Examples 1 to 7 and the sulfide solid electrolytes of Comparative Examples 1 and 2.
[0086] (3) Decrease rate of oxidation current Based on the above (CV measurement (oxidation current)), the oxidation current 2 of the sulfide solid electrolyte obtained in Production Example 1 and the oxidation current 1 of the (modified) sulfide solid electrolyte obtained in the above examples and comparative examples were used to calculate the oxidation current reduction rate using the following formula. Note that the oxidation current 2 in this evaluation is 0.5757 μA. The percentage decrease in oxidation current (%) = (oxidation current 2 - oxidation current 1) / oxidation current 2 × 100 Oxidation current 1: Oxidation current (μA) of the modified sulfide solid electrolyte. Oxidation current 2: Oxidation current (μA) of the sulfide solid electrolyte before modification.
[0087] (4) Ionic conductivity The ionic conductivity was measured as follows: From a sulfide solid electrolyte, a diameter of 10 mm (cross-sectional area S: 0.785 cm²) 2 ), circular pellets with a height (L) of 0.1 to 0.3 cm were formed as samples. Electrode terminals were taken from the top and bottom of the samples, and measurements were taken at 25°C using the AC impedance method (frequency range: 1 MHz to 100 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency region, the real part Z'(Ω) at the point where -Z''(Ω) is minimized was taken as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(mS / cm) was calculated according to the following formula. R = ρ(L / S) σ = 1 / ρ
[0088] [Table 1]
[0089] BET specific surface area is 15m 2 / g or more 35m 2 The modified sulfide solid electrolytes of Examples 1 to 7, which include a sulfide solid electrolyte with a concentration of 0.2 / g or less and a coating material, all exhibit crystallization peak temperatures higher than 265°C, demonstrating excellent heat resistance (see Table 1 and Figure 1). In the CV curves of Figure 2, a decrease in oxidation current was observed for all of the modified sulfide solid electrolytes of Examples 1 to 7, and the rate of decrease in oxidation current was high at 10% or more, indicating excellent oxidation resistance (see Table 1). [Industrial applicability]
[0090] The modified sulfide solid electrolyte of this embodiment has excellent heat resistance and oxidation resistance, as well as high ionic conductivity and excellent battery performance. Therefore, it is particularly suitable for use in lithium-ion batteries, especially in lithium-ion batteries used in automotive applications, as well as in information-related equipment and communication devices such as personal computers, video cameras, and mobile phones, and especially in all-solid-state batteries.
Claims
1. BET specific surface area is 15 m² 2 / g or more 35m 2 It comprises a sulfide solid electrolyte with a concentration of 1 / g or less and a coating material, A modified sulfide solid electrolyte exhibiting a crystallization peak at temperatures above 265°C in the DTA curve obtained by differential thermal analysis (DTA).
2. The modified sulfide solid electrolyte according to claim 1, wherein the content of the coating material is 1.0% by mass or more and 10.0% by mass or less based on 100% by mass of the sulfide solid electrolyte.
3. The modified sulfide solid electrolyte according to claim 1 or 2, wherein the coating material is a compound having an epoxy group.
4. The modified sulfide solid electrolyte according to any one of claims 1 to 3, wherein the sulfide solid electrolyte comprises a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom.
5. The modified sulfide solid electrolyte according to any one of claims 1 to 4, wherein the rate of decrease of the oxidation current measured by cyclic voltammetry (CV measurement), calculated by the following formula, is 10% or more. The rate of decrease in oxidation current (%) = (oxidation current 2 - oxidation current 1) / oxidation current 2 × 100 Oxidation current 1: Oxidation current (μA) of the modified sulfide solid electrolyte. Oxidation current 2: Oxidation current (μA) of the sulfide solid electrolyte before modification.
6. The modified sulfide solid electrolyte according to any one of claims 1 to 5, wherein the sulfide solid electrolyte includes a thiolysicon region type II crystal structure.
Citation Information
Patent Citations
Modified sulfide solid electrolyte and method for producing same
WO2022158458A1